Development of a Forehand Drive Table Tennis Training Model for Juvenile Offenders at the Special Juvenile Rehabilitation Institution in Bengkulu - Andriyani, Mas'ullah; Nopiyanto, Yahya Eko; Rizky, Oddie Barnanda; Sugihartono, Tono; Raibowo, Septian (CV Media Inti Teknologi, 2024)
This research aims to develop a forehand drive training model in table tennis, specifically designed for juvenile inmates at the Bengkulu Special Penitentiary for Children. This research uses a Research and Development (R&D) approach, using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The method used is the descriptive qualitative method. The study population consisted of juvenile inmates in correctional institutions, with a simple random sampling technique. Research instruments include observation, interviews, questionnaires, and documentation. The validation results from experts showed a high level of approval: material experts at 94%, language experts at 90%, and media experts at 92%. The small group trial involving 10 juvenile inmates resulted in an average approval rating of 86%, while the large group trial with 30 participants resulted in an average approval rating of 90%. Based on these findings, it can be concluded that the Table Tennis Forehand Drive Training Model developed for juvenile inmates at the Bengkulu Special Penitentiary for Children is